The Typological Diversity of Morphomes A Cross-Linguistic Study of Unnatural Morphology - Herce, Borja (Oxford University Press, 2023)
This book constitutes the first typologically oriented monograph on morphomes, which is the term given to systematic morphological identities, usually within inflectional paradigms, that do not map onto syntactic or semantic natural classes like 'plural', 'past', 'third-person singular'. Its first half addresses the theoretical and empirical challenges surrounding the identification and definition of morphomes, and surveys their links with related notions like syncretism, homophony, blocking, segmentation, economy, morphophonology, etc. It also presents the different ways in which morphomic structures have been observed to emerge, change, and disappear from a language. The second part of the book contains its core contribution: a database with 120 morphomes across 79 languages from all around the world. These structures are first presented in painstaking philological detail, and then deconstructed into logically independent axes of variation, identified in the spirit of Multivariate Typology. Statistical analysis is then undertaken to spot trends and correlations which are subsequently discussed. Various findings, relevant to both proponents and detractors of Autonomous Morphology, have emerged regarding, for example, the idiosyncratic (i.e. not representative) nature of Romance morphomes, the existence of cross-linguistically recurrent unnatural patterns, and the preference for more natural structures even among morphomes. The database is also expected to allow explorations of other issues, such as how learnability and communicative efficiency pressures impact morphological structure, and lexical and grammatical informativity across the word.